2010
DOI: 10.1002/dvdy.22219
|View full text |Cite
|
Sign up to set email alerts
|

Sec61α is required for dorsal closure during Drosophila embryogenesis through its regulation of Dpp signaling

Abstract: During dorsal closure in Drosophila, signaling events in the dorsalmost row of epidermal cells (DME cells) direct the migration of lateral epidermal sheets towards the dorsal midline where they fuse to enclose the embryo. A Jun amino-terminal kinase (JNK) cascade in the DME cells induces the expression of Decapentaplegic (Dpp). Dpp signaling then regulates the cytoskeleton in the DME cells and amnioserosa to affect the cell shape changes necessary to complete dorsal closure. We identified a mutation in Sec61a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
3
7
0
Order By: Relevance
“…5B and C). Similar patterns of expression have been described for both Sqh and Zip (Franke et al, 2005; Wang and Ward, 2010; Young et al, 1993). In contrast to the specific localization of Sqh1P along the actin cable, Sqh2P is strongly upregulated throughout the DME cells during the initiation phase of dorsal closure (stage 13; Fig.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…5B and C). Similar patterns of expression have been described for both Sqh and Zip (Franke et al, 2005; Wang and Ward, 2010; Young et al, 1993). In contrast to the specific localization of Sqh1P along the actin cable, Sqh2P is strongly upregulated throughout the DME cells during the initiation phase of dorsal closure (stage 13; Fig.…”
Section: Resultssupporting
confidence: 75%
“…We also generated an antibody against full-length Sqh protein to use as a control (initially described in Wang and Ward, 2010). To test the specificity of these antibodies, we conducted western blotting of lysates from wild type imaginal discs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…dVCP, dUFD1L, dNPLOC4, and dSEC61A are essential genes (Leon and McKearin, 1999; Wang and Ward, 2010). Therefore, we used heat shock-inducible in vivo RNAi to deplete these proteins in adult flies and found that depletion of each component of the VCP-UFD1L-NPLOC4 complex as well as SEC61A significantly attenuated SINV infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nrg 17 was identified by absence of immunostaining by Nrg-specific antibodies. Lethal phase and phenotypic analysis of the resulting dead Mcr mutant embryos was performed as described (Wang and Ward, 2010). …”
Section: Materials and Methods Drosophila Strainsmentioning
confidence: 99%